Seakeeping of Recycled Plastic Jerry Can - Based Pontoon Floating Rigid Dock for Estuary Area Application - Prabhawatya Poundra; Rasional Sitepu; Sinung Widiyanto; Bagus Kusuma Aditya; Hadi Suyanto (IPTEK The Journal of Engineering, 2026)
Floating docks provide essential infrastructure for transportation, fisheries, and community activities in estuarine environments, where fluctuating water levels and limited port facilities require stable, economical, and sustainable floating structures. This study investigates the hydrostatic characteristics and seakeeping performance of modular floating rigid dock configurations utilizing recycled 30-L high-density polyethylene (HDPE) plastic jerry cans as buoyancy modules. Three configurations, namely the Base, T-shaped, and U-shaped models, were numerically evaluated using Maxsurf Modeler and Maxsurf Motions under irregular JONSWAP wave conditions. The hydrostatic analysis revealed that the T-shaped and U-shaped configurations increased displacement by approximately 44.3% and 122.3%, respectively, compared with the Base model, while the U-shaped configuration achieved the highest transverse metacentric height (GMt = 2.144 m). Frequency-domain seakeeping analysis showed that the heave and pitch responses of all configurations remained comparable, with differences generally below 10%, indicating that changes in pontoon arrangement had minimal influence on vertical motion characteristics under moderate wave conditions. In contrast, the T-shaped configuration reduced the peak roll response amplitude operator (RAO) by approximately 23% compared with the U-shaped configuration, demonstrating improved transverse motion performance while maintaining comparable heave and pitch responses. Considering hydrostatic capacity, operational stability, structural functionality, and site adaptability, the T-shaped configuration exhibited the most balanced overall performance for estuarine floating dock applications. These findings demonstrate that recycled HDPE plastic jerry cans can serve as technically feasible, sustainable, and low-cost buoyancy modules for modular floating dock systems.